-1
$\begingroup$

Assume that for $a,b>0$ and any $0 < t< 1$

$$ a^tb^{1-t} ≤ ta+(1-t)b $$

Prove given $a_1,a_2,...,a_n ≥ 0$, $b_1,b_2,...,b_n \geq 0$ and $b_1+b_2+...+b_n=1$

We have

$$ \left(\sum_{i = 1}^n\frac{b_i}{a_i}\right)^{-1} \leq \prod_{i = 1}^n a_i^{b_i} \leq \sum_{i = 1}^n b_i*a_i $$

Tried a proof by induction but hit a snag please help

$\endgroup$
  • $\begingroup$ What kind of snag? $\endgroup$ – G Tony Jacobs Apr 17 '14 at 17:21
0
$\begingroup$

Let $c_i = \dfrac{1}{a_i}$, then using weighted AM-GM inequality we have:

$\displaystyle \sum_{k = 1}^n \dfrac{b_k}{a_k} = \displaystyle \sum_{k = 1}^n b_k\cdot c_k \geq \displaystyle \prod_{k=1}^n c_k^{b_k}$. So:

$\displaystyle \sum_{k=1}^n \dfrac{b_k}{a_k}\cdot \displaystyle \prod_{k=1}^n a_k^{b_k} \geq \displaystyle \prod_{k=1}^n (c_k\cdot a_k)^{b_k} = 1$ since $c_k\cdot a_k = 1$ for all $k$'s.

The right inequality is proven by induction on $n$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.